A novel nonsense homozygous variant in the NLGN1 gene found in a pair of monozygotic twin brothers with intellectual disability and autism. Issue 2 (20th November 2018) - Tejada, María‐Isabel; Elcoroaristizabal, Xabier; Ibarluzea, Nekane; Botella, María‐Pilar; de la Hoz, Ana‐Belén; Ocio, Intzane
Abstract :